Environmental and Social Disclosure and Data-Richness in the Mining Industry - Knud Sinding; Philip Peck (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2002)
Self-regulation by firms and industries in relation to the environmental impact they cause is not a full substitute for more traditional regulation of environ-mental externalities. However, some self-regulatory efforts do involve very spe-cific actions that serve to reduce externalities for a specific industry and certainly achieve more than the presentation of a responsible image to the world. An example of such efforts that go beyond common claims about sus-tainable activities, are seen in the increasing numbers of mining firms that generate and issue environmental reports. While there is as yet no indisputable proof that reporting has a direct effect on environmental performance, this pa-per shows that within a single industry there are wide variations in reporting practices and that sincerity is apparent in the process.
Keywords: 330; Umweltbericht; Nachhaltigkeitsbericht; Bergbau; Welt